Colonoscopy Following an Abnormal Fecal Test Result from an Annual Colorectal Cancer Screening Program in a Federally Qualified Health Center - Anne L. Escaron; Joanna Garcia; Amanda F. Petrik; Esmeralda Ruiz; Denis B. Nyongesa; Jamie H. Thompson; Gloria D. Coronado (SAGE Publishing, 2022)
Objective: Individuals with an abnormal fecal immunochemical test (FIT) result have an elevated risk of colorectal cancer, and the risk increases if the follow-up colonoscopy is delayed. Of note, rates of follow-up colonoscopy are alarmingly low in federally qualified health centers (FQHCs), US health care settings that serve a majority racial and ethnic minority patient population. We assessed factors associated with colonoscopy after an abnormal FIT result and used chart-abstracted data to assess reasons (including process measures) for lack of follow-up as part of an annual, mailed-FIT outreach program within a large, Latino-serving FQHC. Methods: As part of the National Institutes of Health-funded PROMPT study, we identified patients with an abnormal FIT result and used logistic regression to assess associations between patient demographics and receipt of follow-up colonoscopy, controlling for patients' preferred language. We report on time (days) to referral and time to colonoscopy. For charts with an abnormal FIT result but no evidence of colonoscopy, we performed a manual abstraction and obtained the reason for the absence of colonoscopy. When there was no evidence of colonoscopy in a patient's electronic health record (EHR), we performed an automated query of the administrative claims database to identify colonoscopy outcomes. Results: We identified 324 patients with abnormal FIT results from July to October 2018. These patients were mostly publicly insured (Medicaid 53.1%, Medicare 14.5%), 81.8% were aged 50 to 64 years, 55.3% were female, 80.3% were Hispanic/Latino, and 67.3% preferred to speak Spanish. We found that 108/324 (33.3%) patients completed colonoscopy within 12 months, and the median time to colonoscopy was 94 days (IQR: 68-176). Common barriers to colonoscopy completion, obtained from chart-abstracted data, were: no documentation following referral to gastrointestinal (GI) specialist or GI consultation (41.6%), no referral to GI specialist following abnormal fecal test (34.2%), and absence of a valid insurance authorization (6.5%). Conclusions: Multi-level strategies are needed to provide optimal care across the cancer continuum for FQHC patients. In order to reduce the risk of CRC and realize the return on fecal testing investment, concerted system-level efforts are urgently needed to improve rates of follow-up colonoscopy among FQHC patients and redress racial and ethnic disparities in CRC screening outcomes.